2020
DOI: 10.1103/physrevd.102.034026
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the doubly radiative decays η()π0γγ and et al.

Abstract: The scalar and vector meson exchange contributions to the doubly radiative decays η ð0Þ → π 0 γγ and η 0 → ηγγ are analyzed within the linear sigma model and vector meson dominance frameworks, respectively. Predictions for the diphoton invariant mass spectra and the associated integrated branching ratios are given and compared with current available experimental data. While a satisfactory description of the shape of the η → π 0 γγ and η 0 → π 0 γγ decay spectra is obtained, thus supporting the validity of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 35 publications
7
27
1
Order By: Relevance
“…was found to be 1.33 × 10 −4 . This result seems in tension with theoretical prediction [12], but more data are needed in order to draw a final conclusion. Dalitz plot analysis of ω → π + π − π 0 provides further constraints to the calculation of electromagnetic transition form factor of ω → π 0 γ * , it is useful to test prediction from dispersive theory [15], and to estimate the so-called crossed-channel effect [16].…”
Section: Search For η → γγη Decaycontrasting
confidence: 62%
See 1 more Smart Citation
“…was found to be 1.33 × 10 −4 . This result seems in tension with theoretical prediction [12], but more data are needed in order to draw a final conclusion. Dalitz plot analysis of ω → π + π − π 0 provides further constraints to the calculation of electromagnetic transition form factor of ω → π 0 γ * , it is useful to test prediction from dispersive theory [15], and to estimate the so-called crossed-channel effect [16].…”
Section: Search For η → γγη Decaycontrasting
confidence: 62%
“…Within the framework of the linear σ model and VDM model, the branching fractions of η → γγπ 0 and η → γγη are predicted to be 3.8×10 −3 and 2.0×10 −4 [12], respectively. Using 1.31×10 9 J/ψ , BESIII determined for the first time the branching fraction B(η → γγπ 0 ) = (32.0 ± 0.7 ± 2.3) × 10 −4 [13] and extracted the non resonant branching fraction (6.16 ± 0.64 ± 0.67) × 10 −4 , which confirmed the theoretical prediction and indicated that this decay was dominated by the VDM processes (ω and ρ contributions dominate).…”
Section: Search For η → γγη Decaymentioning
confidence: 99%
“…[9] an estimation for the electron mode, Γ (η → π 0 e + e − )| box ≥ 1.2 ± 0.2 μeV, which is in accordance with our result, and an estimate for the muon mode, Γ (η → π 0 μ + μ − )| box ≥ 4.3 ± 0.7 μeV, which in this case is incompatible with our calculation. 12 Additionally, Ng et al also presented in Ref.…”
Section: Theoretical Resultsmentioning
confidence: 92%
“…Alternatively, one could have used the theoretical prediction from Ref. [12] Γ (η → π 0 γ γ )| th = 0.17±0.01 eV to obtain Γ (η → π 0 e + e − )/Γ (η → π 0 γ γ ) = (1.6± 0.4) × 10 −5 . 10 The discrepancy with Smith's relative branching ratio might be explained, though, by the effect of p-wave terms that he neglected after admitting that they are not necessarily small.…”
Section: Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation